Differential Wound Healing Capacity of Mesenchymal Stem Cell-Derived Exosomes Originated From Bone Marrow, Adipose Tissue and Umbilical Cord Under Serum- and Xeno-Free Condition - Hoang, Diem Huong; Nguyen, Tu Dac; Nguyen, Hoang-Phuong; Nguyen, Xuan-Hung; Do, Phuong Thi Xuan; Dang, Van Duc; Dam, Phuong Thi Minh; Bui, Hue Thi Hong; Trinh, Mai Quynh; Vu, Duc Minh; Hoang, Nhung Thi My; Thanh, Liem Nguyen; et al. (Frontiers in Molecular Biosciences, 2020)
Exosomes are nano-scale and closed membrane vesicles which are promising for therapeutic applications due to exosome-enclosed therapeutic molecules such as DNA, small RNAs, proteins and lipids. Recently, it has been demonstrated that mesenchymal stem cell (MSC)-derived exosomes have capacity to regulate many biological events associated with wound healing process, such as cell proliferation, cell migration and blood vessel formation. This study investigated the regenerative potentials for cutaneous tissue, in regard to growth factors associated with wound healing and skin cell proliferation and migration, by exosomes released from primary MSCs originated from bone marrow (BM), adipose tissue (AD) and umbilical cord (UC) under serum- and xeno-free condition. We found crucial wound healing-mediated growth factors, such as vascular endothelial growth factor A (VEGF-A), fibroblast growth factor 2 (FGF-2), hepatocyte growth factor (HGF) and platelet-derived growth factor BB (PDGF-BB) in exosomes derived from all three MSC sources. However, expression levels of these growth factors in exosomes were influenced by MSC origins, especially transforming growth factor beta (TGF-β) was only detected in UCMSC-derived exosomes. All exosomes released by three MSCs sources induced keratinocyte and fibroblast proliferation and migration; and, the induction of cell migration is a dependent manner with the higher dose of exosomes was used (20 μg), the faster migration rate was observed. Additionally, the influences of exosomes on cell proliferation and migration was associated with exosome origins and also target cells of exosomes that the greatest induction of primary dermal fibroblasts belongs to BMMSC-derived exosomes and keratinocytes belongs to UCMSC-derived exosomes. Data from this study indicated that BMMSCs and UCMSCs under clinical condition secreted exosomes are promising to develop into therapeutic products for wound healing treatment.